Mimicking Pathogens to Augment the Potency of Liposomal Cancer Vaccines - Nijen Twilhaar, Maarten K. (Pharmaceutics, 2021)
Liposomes have emerged as interesting vehicles in cancer vaccination strategies as their composition enables the inclusion of both hydrophilic and hydrophobic antigens and adjuvants. In addition, liposomes can be decorated with targeting moieties to further resemble pathogenic particles that allow for better engagement with the immune system. However, so far liposomal cancer vaccines have not yet reached their full potential in the clinic. In this review, we summarize recent preclinical studies on liposomal cancer vaccines. We describe the basic ingredients for liposomal cancer vaccines, tumor antigens, and adjuvants, and how their combined inclusion together with targeting moieties potentially derived from pathogens can enhance vaccine immunogenicity. We discuss newly identified antigen-presenting cells in humans and mice that pose as promising targets for cancer vaccines. The lessons learned from these preclinical studies can be applied to enhance the efficacy of liposomal cancer vaccination in the clinic.